Search for sunken treasure / the mummy with no name eaudiobook - Stilton, Geronimo (Geronimo Stilton, 2017)
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. This audiobook features a fast-paced adventure that kids 7-10 will love. NARRATOR: Bill LobleyFORMAT: Unabridged#25: The Search for Sunken TreasureHoley cheese, what an adventure! I was off to the Ratlapagos Islands with my family in search of a long-lost buried treasure. But oh, how I hate traveling! Being on a ship in the middle of the sea wasn't my idea of a "fabumouse" time. And I was beginning to suspect that we weren't the only ones searching for the treasure. . . #26: The Mummy with No Name Halloween and Egypt and mummies . . . oh, my! I admit it, I am a 'fraidy mouse. Halloween scares me out of my fur! But this Halloween, I was heading off on an adventure in one of my very favorite places: Egypt. I couldn't wait to see the sights and soak up some sun far away from New Mouse City. What I didn't realize was that Halloween is popular in Egypt, too — with the mummies, that is!